2014
DOI: 10.1093/jac/dku348
|View full text |Cite
|
Sign up to set email alerts
|

Nevirapine or efavirenz for tuberculosis and HIV coinfected patients: exposure and virological failure relationship*

Abstract: ObjectivesWe describe nevirapine and efavirenz exposure on and off tuberculosis treatment and consequences for virological efficacy and tolerance in patients included in the ANRS 12146/12214-CARINEMO trial.MethodsParticipants were randomly selected to receive either nevirapine at 200 mg twice daily (n = 256) or efavirenz at 600 mg daily (n = 270), both combined with two nucleoside analogues. Blood samples were drawn 12 h after nevirapine or efavirenz administration, while on tuberculosis treatment and after tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Of the 14 studies conducted among adult patients that reported EFV concentrations on and off RH, 10 were in Africa and four in Asia. Notably, among the 10 adult studies conducted in Africa, six reported higher EFV concentration during RH coadministration compared to the off‐RH period, although the difference is highly variable, ranging from 3.7% to 33.3% across studies and countries . The remaining four adult African studies reported a lower EFV concentration while on RH, still with a difference that is highly variable, ranging from –16.3 to –33.3% .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 14 studies conducted among adult patients that reported EFV concentrations on and off RH, 10 were in Africa and four in Asia. Notably, among the 10 adult studies conducted in Africa, six reported higher EFV concentration during RH coadministration compared to the off‐RH period, although the difference is highly variable, ranging from 3.7% to 33.3% across studies and countries . The remaining four adult African studies reported a lower EFV concentration while on RH, still with a difference that is highly variable, ranging from –16.3 to –33.3% .…”
Section: Resultsmentioning
confidence: 99%
“…Of the total 119 records retrieved, 22 records were included in the analysis (Figure 1). Of these, 20 studies had data on at least mean or median EFV C 12 (n = 16) or predose C min (n = 6) measured either in the morning (n = 4) or evening (n = 2) during RH coadministration [17,35,38,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], while one study only reported body weight-specific EFV C 12 data during RH coadministration [66] and one reported only proportions of patients with subtherapeutic EFV concentrations [67]. Table 1 shows characteristics of the 22 included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevirapine is metabolized by both CYP3A4 and CYP2B6 [87]. Nevirapine plasma concentration declined when co-administered with RIF [88, 89]. Efavirenz is metabolized mainly by CYP2B6, an enzyme that is upregulated by PXR [55, 90, 91].…”
Section: 0 Pxr On Drug Metabolism and Dispositionmentioning
confidence: 99%
“…Efavirenz is metabolized mainly by CYP2B6, an enzyme that is upregulated by PXR [55, 90, 91]. However, the data are inconsistent with a clinically significant effect of RIF on efavirenz metabolism [89, 92]. …”
Section: 0 Pxr On Drug Metabolism and Dispositionmentioning
confidence: 99%